Conflict in Organization: A Re-Examination - Litterer, Joseph A. (Academy of Management Journal, 1966)
Generally, conflict in organizations is condemned. This article examines some of the functions which conflict can fill and also some of its roots. It is shown that the roots of conflict are embedded in some of the basic characteristics of organizations, and hence it is to some degree inescapable. It is also shown that conflict can have useful effects in organizations. Essentially, the article shows that conflict is a controllable element in organizations, and can, therefore, be adjusted to minimize its dysfunctional and maximize its functional characteristics.